2019
DOI: 10.1002/jms.4232
|View full text |Cite
|
Sign up to set email alerts
|

A fast and simple approach for the quantification of 40 illicit drugs, medicines, and pesticides in blood and urine samples by UHPLC‐MS/MS

Abstract: Based on data collected by the “Information System on Diseases of Compulsory Declaration”, an agency responsible for poisoning notifications in Brazil, just short of 500,000 humans in that country were exposed to xenobiotics during the period 2013‐2017. The most commonly detected substances included medications (e.g., analgesics, benzodiazepines, antidepressants, anticonvulsants), drugs of abuse and pesticides. In this month's Special Feature, a group of investigators report a fast and simple UHPLC‐MS/MS appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(18,19) However, as technology has improved, mass spectrometers have become cheaper and faster. (18,23,29,(39)(40)(41) A study by Caspar et al demonstrated its value in 24/7 toxicology by analysing 22 drugs and active metabolites in a qualitative and quantitative manner. (30) In the study done be Caspar et al, the total run time for a test was 11 minutes, extrapolated to the emergency care setting, such run times would enable the clinician to treat the patient accordingly and in a timely point-of-care manner.…”
Section: Discussionmentioning
confidence: 99%
“…(18,19) However, as technology has improved, mass spectrometers have become cheaper and faster. (18,23,29,(39)(40)(41) A study by Caspar et al demonstrated its value in 24/7 toxicology by analysing 22 drugs and active metabolites in a qualitative and quantitative manner. (30) In the study done be Caspar et al, the total run time for a test was 11 minutes, extrapolated to the emergency care setting, such run times would enable the clinician to treat the patient accordingly and in a timely point-of-care manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recent times have shown an increasing number of intoxication cases, resulting in damaging public health issues all around the globe, and Brazil is not an exception [ 1 ]. Most of the cases observed denoted the use of psychoactive substances, such as recreational drugs and medication for psychiatric use [ 2 ].…”
Section: Dear Editormentioning
confidence: 99%